SISTEM PENDUKUNG KEPUTUSAN PENENTUAN DOSEN PEMBIMBING SKRIPSI MENGGUNAKAN METODE PROFILE MATCHING (STUDI KASUS : UNIVERSITAS PAMULANG) - Miftahurrahman Al Muhdi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Universities that have a busy concentration in teaching and learning activities are the study programs. The study program carries out lecture activities from start to finish. In the process of completing the study, a student must compile a scientific work (thesis) which will later be accounted for during the court hearing in front of the examiners. The process of writing a thesis for each student is directed by 2 thesis supervisors. The process of preparing the submission of the thesis title until the issuance of the thesis supervisor's statement is fully carried out by the study program, With so many students submitting thesis titles and the content of knowledge from each submitted title, it is quite a complicated job to determine the relevant supervisor between the academic abilities of the lecturer and the title being mentored The application of the decision support system for the determination of the thesis supervisor for students of the S1-Informatics Engineering study program will be analyzed for system socialization, system implementation, and ends with an analysis of the influence of the decision support application system in determining the thesis supervisor on the quality of study program services. The output of this research is a decision support system software for determining thesis supervisors so that the study program can more easily determine and distribute supervising lecturers for each student who submits a thesis title quickly, precisely and accurately.